Factors influencing women in physical activity programs in Malaysia. (11th December 2017) - Hanlon, C; Khoo, S; Morris, T; Eime, R
Summary: The majority of research on factors associated with women participation in physical activity (PA) has been in developed countries with limited research in developing countries. Few women in Malaysia are active at the recommended levels for health, and activity rates are less than developed countries. Little research has focused specially on physically active Malaysian women and the factors that contribute to them becoming and staying active in PA programs. This lack of knowledge hinders the tailored development and implementation of PA programs to meet their needs. The aim of this study was to identify the factors of participation in PA programs for Malaysian women. The social–ecological model was used to investigate and theme the factors. Focus group discussion was conducted with participants in six PA programs targeted specifically to women. Thirty-seven women were involved in the focus group discussion, with ages ranging from 19 to 82 years. Inductive and deductive content analysis was conducted from verbatim transcripts using NVivo. Inductive content analysis allowed raw data and second-order themes to emerge. Findings revealed social support structures, tailored programs for women, and location were key contributors that encouraged women to participate in these programs. The similarity in contributors between women in non-western and western countries signifies a prime opportunity for bi-lateral relationships to be formed to enable the enhancement of program development relevant to different ethnicities and cultures within or across countries.